Sympathoadrenergic modulation of hematopoiesis: a review of available evidence and of therapeutic perspectives - Cosentino, Marco; Marino, Franca; Maestroni, Georges J. M. (Frontiers in Cellular Neuroscience, 2015)
Innervation of the bone marrow (BM) has been described more than one century ago, however the first in vivo evidence that sympathoadrenergic fibers have a role in hematopoiesis dates back to less than 25 years ago. Evidence has since increased showing that adrenergic nerves in the BM release noradrenaline and possibly also dopamine, which act on adrenoceptors and dopaminergic receptors expressed on hematopoietic cells and affect cell survival, proliferation, migration and engraftment ability. Remarkably, dysregulation of adrenergic fibers to the BM is associated with hematopoietic disturbances and myeloproliferative disease. Several adrenergic and dopaminergic agents are already in clinical use for non-hematological indications and with a usually favourable risk-benefit profile, and are therefore potential candidates for non-conventional modulation of hematopoiesis.